PENGARUH GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA KARYAWAN PADA KOPERASI PT. PELAYARAN TONASA LINES KABUPATEN PANGKEP - R, Masmarulan; Yasin, Nurfatwa Andriani; Kurniawaty, Kurniawaty (Universitas Muhammadiyah Parepare, 2021)
PT. Pelayaran Tonasa Lines in Pangkep Regency is a company engaged in commercial and industrial equipment which is required to compete with other companies in the same field. Therefore, it needs a leader who can encourage its employees. This research aims to determine the effect of autocratic leadership style, participatory leadership style, and delegation leadership style on employee morale at the Cooperative PT. Pelayaran Tonasa Lines in Pangkep Regency. It was expected to find an appropriate leadership style for the cooperative PT. Pelayaran Tonasa Lines in Pangkep Regency. The impacts of each company's operational activities will automatically affect the environment and the community around the company running its business. One of the operational activities in the company is the production data analysis method used is multiple regression analysis. The research object was all employees of the cooperative PT. Pelayaran Tonasa Lines in Pangkep Regency that consisted of 49 people. The results showed autocratic leadership style had a negative and insignificant effect on employee morale, while the participatory leadership style and the delegation leadership style had a positive and significant impact on employee morale at the cooperative PT. Pelayaran Tonasa Lines in Pangkep Regency. The company's leader must establish appropriate intense communication among all employees so that problems and organizational development can be overcome jointly.